Anti-Mullerian Hormone Levels in Regularly Menstruating Nigerian Women - Olawale OO; Dada VO; Abbiyesuku FM; Eluyera OO; Olooto EW; Osuji KC (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Studies have shown that serum levels of Anti-Mullerian Hormones (AMH) decrease with age as it is also an early and sensitive marker of ovarian reserve in women in the North American, European and Asian regions. Various research works have also generated data about AMH in the Caucasian, Americans and Asians There was a need to compare these known data with African data. Objectives: To assess the serum levels of AMH in healthy women of reproductive age and determine the relationship between AMH, age, Body Mass Index, parity and menstrual cycle in healthy regularly menstruating women. Methods: A cross-sectional study of 200 apparently healthy women aged 21-45 years was carried out between January and May 2014. Serum AMH and FSH levels were measured in the participants using Enzyme-Linked Immunosorbent Assay. Results: The median AMH value was 4.07ng/mL, while the median FSH value was 9.65mIU/mL. The reference 90% CI of AMH was 0.60 -9.71 ng/ml. There was a significant negative correlation between serum level of AMH and age (r = - 0.718, p<0.001). Conclusion: The serum AMH levels gradually declined throughout the reproductive lifespan of a woman.